2023
DOI: 10.1038/s41586-023-06549-9
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic ferret models define pulmonary ionocyte diversity and function

Feng Yuan,
Grace N. Gasser,
Evan Lemire
et al.

Abstract: Speciation leads to adaptive changes in organ cellular physiology and creates challenges for studying rare cell-type functions that diverge between humans and mice. Rare cystic fibrosis transmembrane conductance regulator (CFTR)-rich pulmonary ionocytes exist throughout the cartilaginous airways of humans1,2, but limited presence and divergent biology in the proximal trachea of mice has prevented the use of traditional transgenic models to elucidate ionocyte functions in the airway. Here we describe the creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Using conditional genetics allowed the identification of three subtypes of pulmonary ionocytes and the confirmation of their CFTR-dependent function. In fact, this work highlights the role of ionocytes in supporting a movement of Cl − and HCO 3 − that was found to be cell-autonomous, thus providing unique layers in the regulation of ASL volume, PH and viscosity, thus contributing to effective mucociliary clearance ( Yuan et al, 2023 ).…”
Section: Cell Type-specific Regulation Of Cftrmentioning
confidence: 82%
“…Using conditional genetics allowed the identification of three subtypes of pulmonary ionocytes and the confirmation of their CFTR-dependent function. In fact, this work highlights the role of ionocytes in supporting a movement of Cl − and HCO 3 − that was found to be cell-autonomous, thus providing unique layers in the regulation of ASL volume, PH and viscosity, thus contributing to effective mucociliary clearance ( Yuan et al, 2023 ).…”
Section: Cell Type-specific Regulation Of Cftrmentioning
confidence: 82%
“…Lei et al ( Lei et al, 2023 ) demonstrated that apical membrane CFTR Cl − channels collaborate with basolateral membrane barttin/ClC-K Cl − channels in ionocytes for transepithelial Cl − absorption, leading to fluid absorption. Moreover, FOXI1-knockout and CF ferrets both display reduced ASL volume and impaired mucociliary clearance due to ASL abnormalities, including slow fluid absorption but also absent fluid secretion, lack of CFTR-mediated ASL alkalization and increased mucus viscosity ( Yuan et al, 2023 ). Therefore, albeit less than about 1% of total epithelial cells in airways ( Montoro et al, 2018 ; Plasschaert et al, 2018 ; Lei et al, 2023 ), ionocytes regulate ASL homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 The CF ferret model manifests lung disease that resembles the pathologies found in people with CF. 18 , 19 , 20 , 21 , 22 Given the availability of CF ferrets for preclinical studies, a better understanding of rAAV2.5T immunology and durability of transgene expression in ferret lungs is needed prior to embarking on studies in diseased CF animals.…”
Section: Introductionmentioning
confidence: 99%